(untitled) (Journal of Comparative & International Higher Education, 2024)
International students in U.S. higher education who pursue work must balance personal and professional pressures while seeking employment. While much attention has been given to their experiences of acculturation, stress, and psychological well being, further work is needed to document experiences of seeking employment. This phenomenological study utilized semi-structured interviews to explore international students’ experiences of personal growth and change, economic pressures, and seeking employment in the US. The results indicate that international students share many of the same experiences of personal change of their domestic counterparts while simultaneously navigating a new cultural context, deal with differing levels and a variety of sources of economic pressure, and navigate barriers to their employment search rooted in the lack of clear information, misaligned support resources, personal shortcomings, employer perceptions, and visa restrictions.